Manipulating Topological Domain Boundaries in the Single-Layer Quantum Spin Hall Insulator 1T '-WSe2 - Pedramrazi, Zahra; Herbig, Charlotte; Pulkin, Artem; Tang, Shujie; Phillips, Madeleine; Wong, Dillon; Ryu, Hyejin; Pizzochero, Michele; Chen, Yi; Wang, Feng; Mele, Eugene J.; Shen, Zhi-Xun; et al. (AMER CHEMICAL SOC, 2019)
We report the creation and manipulation of structural phase boundaries in the single-layer quantum spin Hall insulator 1T'-WSe2 by means of scanning tunneling microscope tip pulses. We observe the formation of one-dimensional interfaces between topologically nontrivial 1T' domains having different rotational orientations, as well as induced interfaces between topologically nontrivial 1T' and topologically trivial 1H phases. Scanning tunneling spectroscopy measurements show that 1T'/1T' interface states are localized at domain boundaries, consistent with theoretically predicted unprotected interface modes that form dispersive bands in and around the energy gap of this quantum spin Hall insulator. We observe a qualitative difference in the experimental spectral line shape between topologically "unprotected" states at 1T'/IT' domain boundaries and protected states at 1T'/1H and 1T'/vacuum boundaries in single-layer WSe2.
Keywords: PHASE-TRANSITION; MONOLAYER; RESISTANCE